2018
DOI: 10.1039/c8cc05068f
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-immobilized metal–organic framework nanosheets as tandem catalysts for the generation of nitric oxide

Abstract: An enzyme-immobilized metal-organic framework (MOF) nanosheet system was developed as a tandem catalyst, which converted glucose into gluconic acid and H2O2, and sequentially the latter could be used to catalyze the oxidation of l-arginine to generate nitric oxide in the presence of porphyrinic MOFs as artificial enzymes under physiological pH, showing great potential in cancer depleting glucose for starving-like/gas therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 40 publications
1
22
0
2
Order By: Relevance
“…Targeting the overexpression of glucose in cancer cells, a novel concept named starvation therapy is performed by glucose depletion with GOx . The desirable loading efficiency and well‐preserved enzymatic activity of GOx into MOFs, allows it to more efficiently biocatalyze the conversion of endogenous glucose in cancer cells . Meanwhile, it has been demonstrated that the combination of different therapeutic ways (e.g.…”
Section: Applicationsmentioning
confidence: 99%
“…Targeting the overexpression of glucose in cancer cells, a novel concept named starvation therapy is performed by glucose depletion with GOx . The desirable loading efficiency and well‐preserved enzymatic activity of GOx into MOFs, allows it to more efficiently biocatalyze the conversion of endogenous glucose in cancer cells . Meanwhile, it has been demonstrated that the combination of different therapeutic ways (e.g.…”
Section: Applicationsmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are a new kind of organic-inorganic hybrid porous material [23,24]. Since MOF materials are considered to be potent supporting matrices for enzyme immobilization, many kinds of commodity enzymes were immobilized successfully [25][26][27][28]. However, other researchers have spent their energy on the design of Zn 2+ , Cu 2+ or Fe 3+ -based MOFs for enzyme immobilization [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…There has been growing interest in the use of MOFs for tandem catalysis 36 38 with recent reports of MONs being used alongside nanoparticles and enzymes to facilitate multistep reactions. 9,10,39 As Cu(ABDC-PS) is partially functionalised with sulfonic acid groups, with basic amine sites remaining, we decided to investigate their ability to catalyse a well-known acid-base tandem reaction. 34,40,41 Cu(ABDC-PS) was tested as a catalyst for the acid hydrolysis of benzaldehyde dimethyl acetal (1) to benzaldehyde (2), followed by a Knoevenagel condensation to form benzylidene malononitrile (3).…”
mentioning
confidence: 99%